Perdas de rendimento do girassol devidas ao ataque de pássaros - Siqueira, Patricia Liany de Oliveira Fernandes (2017)
Sunflower damage caused by bird attacks occur in the major producing regions of the world, making birds important pest of the sunflower crop.The objective of the present work was to estimate yield, yield losses due to bird attack and phenotypic correlations between characters of sunflower cultivars and to estimate the direct and indirect effects of the main character yield and percentage of yield loss with the other characteristics. The experimental design was a randomized block design with five replicates. Grain yield, number of grains and the 1000 seeds were assessed in subdivided parcels where the cultivars were assigned parcels and the protection of capitulum to the attack of birds (with and without cover) were assigned to subplots. The other evaluated characteristics were analyzed in a simple DBC. There was interaction cultivar x bird attack. The cultivars Neon 15 and Olisun showed higher grain yields in the covered plots and Neon 15 cultivars and aguará 05 had higher yield in the plots without coverage. The cultivars Aguará 05 and CF 101 were less attacked and probably more resistant to bird attack. The reduction caused by bird attack was approximately 631.6 kg ha-1, estimating a 25% loss in grain yield. The most affected cultivars with the highest loss percentage were Hélio 253 and Hélio 358. The characteristics stem diameter, plant height, capitulum diameter, number of grains per capitulum, initial and full flowering showed a positive direct effect on the yield of grains (with cover) and the characteristic mass of 1000 grains presented positive correlation with% loss. The cock of the meadow was the bird species that occurred as a pest in the experimental area